PERFORMANCE ANALYSIS OF BTS (BASE TRANSCEIVER STATION) VIEWED FROM THE INFLUENCE OF LARGE DIAMETER MICROWAVE ANTENNA - Fitri Imansyah; Iqbal Arsyad; Eko Sarwono; Eko Julianto (Fakultas Teknik UM Pontianak, 2023)
Microwave is an electromagnetic wave which is a form of radio emission that is transmitted through the air and received using a circular antenna mounted on a tower. The microwave antenna functions to receive and distribute radio waves, either from BTS to BTS or from BTS to BSC. BTS performance itself is influenced by the size of the diameter of the microwave antenna. The purpose of this research was to determine the effect of the diameter of a microwave antenna on BTS performance by comparing the diameter at several different locations with the same type of provider. As for the signal parameter values, they are adjusted to the link budget calculation, which will later be compared with the data monitored via StarWeb LCT, so that the data or signal can be transmitted optimally. Based on the results of the analysis, the diameter of the microwave antenna affects the RSL value, frequency, and transmitting distance of the signal. A microwave antenna with a diameter of 0.3 m can transmit signals as far as 1-2 km, a diameter of 0.6 m can transmit signals as far as 3-4 km, a diameter of 0.9 m can transmit signals as far as 9-12 km, and a diameter of 1.8 m can transmit signals as far as 17-12 km. 19 km, which means that the larger the size of the microwave antenna used, the farther the signal transmission distance will be.